An Alternative Approach for Perioperative Extracorporeal Life Support Implantation. Issue 8 (24th April 2015) - Saeed, Diyar; Maxhera, Bujar; Westenfeld, Ralf; Lichtenberg, Artur; Albert, Alexander
Abstract Central veno‐arterial extracorporeal membrane oxygenation (ECMO) is traditionally implanted using direct cannulation of the aorta and right atrium. We aim to summarize the outcome of patients who underwent perioperative central ECMO implantation using an alternative surgical approach, which allows sternum closure and does not require resternotomy at the time of explantation. We retrospectively reviewed patients who required veno‐arterial ECMO support at our institution between January 2013 and July 2014. Inclusion criteria were patients undergoing central ECMO implantation using the above‐mentioned implantation technique. Nine patients (65 ± 14 years) were supported using this technique. Four patients underwent coronary bypass surgery as a primary surgery and the other five patients had combined coronary and valve surgeries. The average duration of ECMO support was 9 ± 7 days (range 1–24 days). The dominant postoperative complication was renal failure, which occurred in eight patients (89%). In four patients (44%), the ECMO was successfully removed. Survival rate to discharge was 22%. In conclusion, this study showed the feasibility of this alternative ECMO implantation technique. No technical issues were encountered. Extended support duration and reducing resternotomy risks may be the main advantages of this technique compared with conventional ECMO implantation methods.